vasQchip: a novel microfluidic, artificial blood vessel scaffold for vascularized 3D tissues - Kappings, Vanessa; Grün, Christoph; Ivannikov, Darja; Hebeiß, Isabella; Rapp, Bastian E.; Hettel, Matthias; Deutschmann, Olaf; Schepers, Ute (Advanced Materials Technologies, 2018)
To date, tissue engineering and organ-on-a-chip devices become more powerful as replacements for animal testings in high throughput drug screenings. However, the majority of the devices are either based on static 2D or 3D cell cultures or on microfluidic channel systems that are usually rectangular and do not fit to the geometry of natural blood vessels. Therefore, a semicircular microfluidic blood vessel scaffold (vasQchip) with a surrounding microfluidic compartment for vascularized 3D cell culture was developed, which resembles the curvature of natural blood vessels. vasQchip is composed of a porous microchannel which is produced by micro-thermoforming of polycarbonate membranes. The pores generated by ion track technology allow for the support of nutrients and gases as well as for the exchange of growth factors or immune cells with the surrounding compartment. Eventually the surrounding compartment can be used for the establishment of 3D cell cultures in order to reconstruct vascularized tissues. Here, the vasQchip for its biocompatibility is characterized to somatic primary cells, the diffusion of molecules through the artificial blood vessels and its suitability for 3D cell culture. In addition, shear stress and flow regimes are simulated in order to mimic the natural environment of vascularized tissues.
Gesehen am 20.09.2018